1990
DOI: 10.1128/jcm.28.8.1708-1710.1990
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by calcium of the detection of cytomegalovirus in cells treated with dexamethasone and dimethyl sulfoxide

Abstract: MRC-5 cultures treated with dexamethasone, dimethyl sulfoxide, and calcium were compared with untreated cultures and cultures treated with dexamethasone and dimethyl sulfoxide for the detection of human cytomegalovirus by the shell vial method. The addition of calcium resulted in significantly increased growth of human cytomegalovirus AD169. Protein studies and cell counts showed renewed cell proliferation in the treated cultures. When low-titer clinical specimens were retested, 27.5% of all positives revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
3
14
1
Order By: Relevance
“…Sensitivity can be increased even further by the inclusion of 2 mM calcium in the medium in the latter two steps (9). MRC-5 cells grown in shell vials from Whittaker Bioproducts were used in those experiments (8,9). Similar results were seen by investigators using MRC-5 cells grown in their own laboratory and treated with DEX alone (7).…”
Section: Evaluation Of Manufacturer's Recommended Growth Value Threshmentioning
confidence: 79%
See 2 more Smart Citations
“…Sensitivity can be increased even further by the inclusion of 2 mM calcium in the medium in the latter two steps (9). MRC-5 cells grown in shell vials from Whittaker Bioproducts were used in those experiments (8,9). Similar results were seen by investigators using MRC-5 cells grown in their own laboratory and treated with DEX alone (7).…”
Section: Evaluation Of Manufacturer's Recommended Growth Value Threshmentioning
confidence: 79%
“…Studies in our laboratory have shown that this sensitivity can be increased by pretreatment of the cells with medium containing dexamethasone (DEX) and by the addition of DEX plus dimethyl sulfoxide (DMSO) to the centrifugation and incubation steps (8). Sensitivity can be increased even further by the inclusion of 2 mM calcium in the medium in the latter two steps (9). MRC-5 cells grown in shell vials from Whittaker Bioproducts were used in those experiments (8,9).…”
Section: Evaluation Of Manufacturer's Recommended Growth Value Threshmentioning
confidence: 99%
See 1 more Smart Citation
“…MRC-5 cells were infected with CMV at a multiplicity of infection (MOI) of ≈ 0·02 for 2 h followed by the addition of MRC-5 growth medium supplemented with 2 m M calcium chloride (Sigma), 1% dimethylsulphoxide (DMSO) (Sigma) and 0·01 m M dexamethasone (Sigma) to enhance CMV replication [14]. The cells were collected 48 h postinfection by trypsinization, washed to remove extracellular virus and suspended in MEM.…”
Section: Production Of Cmv-infected Cell Linesmentioning
confidence: 99%
“…MRC-5 cells, which are highly susceptible to spreading CMV infection [14], were used to model leucocytes actively replicating the virus. Real-time quantification of intracellular CMV DNA showed that gamma irradiation had no discernable effect on reducing the virus load immediately after treatment.…”
Section: Effect Of Gamma Irradiation and Pen110 Treatment On Active Cmentioning
confidence: 99%